Tuberculosis new scenery: prison establishments - Zarate, Eduardo (2005)
This is a review on the incidence of tuberculosis (TBC) y human immunodeficiency virus (HIV) in imprisoned persons. These incidences are higher in the main Peruvian penitentiary establishments than in the general population. We review the contributing conditions and a differentiated strategy for those populations at risk is proposed: a capacitating intervention of health professionals, health promoters formation, and intense use of health information, education and communication.